PENGARUH ASET PAJAK TANGGUHAN, BEBAN PAJAK TANGGUHAN DAN PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di BEI Tahun 2011-2013) - Fitriany, Lucy Citra; Nasir, Azwir; Ilham, Elfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to determine the influence of current deffered tax asset, deffered tax expense and tax planning on earnings management. Independent variables used in this study are current deffered tax asset, deffered tax expense and tax planning, while the dependent variable in this study is earnings management are measured using discretionary accrual (DA). Populations used in this study is manufacture companies listed on IDX 2011-2013, where the total population is used by 16 companies. The sampling technique used was purposive sampling technique in which the number of observations obtained this study was 48 (16x3). Data analysis conducted with Binary logistic regression model with help of software SPSS version 20,0. Of the result of the testing that has been done, the wall test showed that the independent variables current deffered tax asset and tax planning which has a significant influence on earnings management, while the deffered tax expense variables did not significantly affect the earnings management.Keywords : Earnings Management, Current Deffered Tax Asset, Deffered Tax Expense and Tax Planning.